Correlated Noise Description Using HDLs. Issue 1 (2015) - Haase, Joachim; Lange, André
Abstract: There exist several problems where only a frequency-domain characteristic is given, for instance the description of the terminal behaviour by frequency-dependent parameters, and where we are only interested in the results of a small-signal frequency-domain analysis. Therefore, we show how to make use of an extended small-signal modelling approach to describe any small-signal behaviour in particular correlated noise sources using hardware description languages (HDLs) such as the Verilog-AMS and VHDL-AMS behavioural modelling languages.